Catalytic Reduction of ortho- and para-Azidonitrobenzenes via tert-Butoxide Ion Mediated Electron Transfer - Burnley, James; Carbone, Giorgio; Moses, John E. (Synlett, 2013)
The reduction of a range of substituted azidonitrobenzene derivatives to the corresponding aniline is described. The chemoselective reaction proceeds cleanly and in good yield, generating minimal waste products. The process involves a thiazolium salt derived species which is proposed as a radical anion relay, with tert-butoxide as the stoichiometric reductant.
Keywords: azide; reduction; tert-butoxide; electron transfer; N-heterocyclic carbene